Afiks Pembentuk Verba dalam Narasi Dubing di Media Online Riau Televisi - Fauziah, Indah; Faizah, Hasnah; Charlina, Charlina (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
Dubbing narrative is a complementary text to an online news media which has various variations of verb-forming affixes for each word that is formed. This research aims to describe the form, formation process and grammatical meaning of verb-forming affixes in dubbed narratives in the online media Riau Televisi. The method used in the research is descriptive qualitative. Research data was obtained from dubbing narratives on Riau Televisi's online media, namely riautelevisi.com. The data collection technique used was note-taking. The research data analysis technique is implementing qualitative analysis in the form of data reduction, data display, and conclusion drawing/verification. The results of the research show that dubbing narratives in the online media Riau Televisi contain various verb-forming affixes, namely: prefix ber-, prefix meN-, prefix di-, prefix ter-, prefix ke-, prefix per-, suffix -kan, suffix -i, confix per-kan, confix per-i, confix ke-an, clofix ber-kan, and confix and clofix ber-an. The process of verb formation includes maintaining the /r/ phoneme, deleting the /r/ phoneme, changing the /r/ phoneme to /l/, adding the nasal phoneme /n/, adding the nasal phoneme /m/, retaining the phoneme, weakening the phoneme, changing the phoneme /N/ becomes /ñ/), addition of nasal phoneme /ng/, addition of nasal phoneme /nge/, and phoneme shift. The grammatical meaning of verb-forming affixes cannot be separated from the form of the affix and the components of the basic morpheme that are given the affix.